2002
DOI: 10.1038/sj.onc.1205789
|View full text |Cite
|
Sign up to set email alerts
|

Long-patch base excision repair of apurinic/apyrimidinic site DNA is decreased in mouse embryonic fibroblast cell lines treated with plumbagin: involvement of cyclin-dependent kinase inhibitor p21Waf-1/Cip-1

Abstract: Molecular interactions among cell cycle and DNA repair proteins have been described, but the impact of many of these interactions on cell cycle control and DNA repair remains unclear. The cyclin-dependent kinase inhibitor, p21, is known to be involved in DNA damage-induced cell cycle arrest and blocking DNA replication and repair. Participation of p21 has been implicated in nucleotide excision repair. However, the role of p21 in the base excision repair (BER) pathway has not been thoroughly studied. In the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 67 publications
3
37
0
Order By: Relevance
“…This assay system utilizes a known type of DNA damage introduced in a p21P promoter whose activity can be monitored to assess the efficiency of the repair in the cell. As described previously, we randomly modified C residues of the p21P promoter to a reduced abasic site (R-p21P) plasmid by chemical and enzymatic modification (Jaiswal et al, 2002). The reduced abasic site of the R-p21P plasmid can be repaired by the LP-BER pathway involving pol-b.…”
Section: Discussionmentioning
confidence: 99%
“…This assay system utilizes a known type of DNA damage introduced in a p21P promoter whose activity can be monitored to assess the efficiency of the repair in the cell. As described previously, we randomly modified C residues of the p21P promoter to a reduced abasic site (R-p21P) plasmid by chemical and enzymatic modification (Jaiswal et al, 2002). The reduced abasic site of the R-p21P plasmid can be repaired by the LP-BER pathway involving pol-b.…”
Section: Discussionmentioning
confidence: 99%
“…Plumbagin alone has been shown to induce apoptosis in different cell types (13,14,18), and that may also be linked to the suppression of NF-B. Invasion and metastasis require the expression of MMP-9 and COX-2, all of which were modulated by plumbagin.…”
Section: Discussionmentioning
confidence: 99%
“…Sugie et al (12) have shown that plumbagin significantly inhibited azoxymethane-induced intestinal carcinogenesis in rats, suggesting its chemopreventive activity (12). Plumbagin has also been shown to induce S-G 2 /M cell cycle arrest through the induction of p21 (an inhibitor of cyclin-dependent kinase) (13). A recent report showed that plumbagin has a chemotherapeutic potential as an anticancer agent in ovarian cancer cells with the mutated BRCA1 gene (14).…”
mentioning
confidence: 99%
“…In addition, p21 can bind to proliferating cell nuclear antigen, thereby blocking DNA synthesis (Gartel and Radhakrishnan, 2005). Jaiswal et al (2002) have indicated that plumbagin treatment caused an increase of p21 expression and a decrease of DNA repair resulting in cell death in mouse embryonic fibroblast cells. However, p21 has also been reported to influence the outcome of the p53 response to DNA damage and play a protective role on survival signal against apoptosis (Seoane et al, 2002;Kuo et al, 2004).…”
Section: Discussionmentioning
confidence: 99%